Innovation performance of European SMEs: determined by regional or firm specific factors? - Makrevska disoska, Elena; Toshevska trpchevska, Katerina (Inderscience Enterprises Ltd., 2019)
Different factors determine the innovation behaviour of Europe an SMEs firms. The goal of this paper is to assess the impact of firm specific and regional specific factors on the innovation behaviour of the firms in Europe. The analysis is based on data from the Regional Innovation Scoreboard for 2017, particularly focusing on the performance of small and medium-sized enterprises (SMEs). The OLS regression shows that firm specific factors are of greater importance for the European firms in the observed regions. That suggests that regional environment is not an independent determinant of firms’ innovation activity. Innovation activity is shaped by the characteristics of the firms. The regional innovation policies should focus more on the specific needs of the firms and help them realise their existing and unexploited innovation potential.
Keywords: innovation performance; regional specific factors; firm specific factors; European SMEs